THE INFLUENCE OF COMPENSATION, JOB INVOLVEMENT, AND ROLE CONFLICT ON EMPLOYEE PERFORMANCE VIA INTRINSIC MOTIVATION AS AN INTERVENING VARIABLE AT THE BATAM CITY EDUCATION OFFICE - Happy Wi Jan Eight Simatupang; Ramli; Sarmini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to examine the effects of compensation, job involvement, and role conflict on employee performance, with intrinsic motivation serving as an intervening variable, at the Batam City Education Office. A quantitative research approach was employed using a survey method involving 158 employees of the Batam City Education Office. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and multiple linear regression analysis. The findings indicate that compensation has a positive and significant effect on employee performance, job involvement has a positive and significant effect on employee performance, role conflict has a positive and significant effect on employee performance, and intrinsic motivation has a positive and significant effect on employee performance. With respect to intrinsic motivation, compensation demonstrates a positive but statistically insignificant effect, while job involvement exhibits a negative and statistically insignificant effect. In contrast, role conflict exerts a positive and significant effect on intrinsic motivation. Simultaneously, compensation, job involvement, and role conflict significantly influence intrinsic motivation and employee performance. Furthermore, the mediation analysis reveals that intrinsic motivation does not mediate the relationship between compensation and employee performance, nor between job involvement and employee performance. However, intrinsic motivation positively and significantly mediates the relationship between role conflict and employee. The study concludes that improving employee performance is more effectively achieved through enhancing job involvement, constructively managing role conflict, and strengthening employees’ intrinsic motivation rather than relying solely on compensation improvements. These findings provide both theoretical and practical contributions to human resource management, particularly within public sector organizations, by highlighting the strategic role of intrinsic motivation in explaining the relationship between organizational factors and employee performance.